'The salvation of them': emigration to North America from the nineteenth-century Irish women's convict prison. Issue 4 (3rd July 2016) - Farrell, Elaine
ABSTRACT: The systematic transportation of criminals from Ireland to the colonies ceased in 1853 and was officially abolished by the Penal Servitude Act of 1857. Yet this did not end the international movement of Irish women from the convict prison. Using the gratuity earned through their industry, and with the assistance of the prison department, religious men and women, philanthropic societies, or family members and friends, women departed Ireland from the convict prison. Assistance took the form of passage tickets, money, clothing or provisions for the trip, accommodation before or after the journey, as well as contacts in the new world. This article, based on the overseas movement of discharged female prisoners in the wake of transportation, argues that emigration from prison was not an attempt to export Ireland's serial offenders. While the Irish authorities might have wished to rid Ireland of women with criminal records, increasingly rigid immigration regulations prevented this practice from developing on a large scale.